Decreased levels of serum glutathione peroxidase 3 are associated with papillary serous ovarian cancer and disease progression - Agnani Deep; Camacho-Vanegas Olga; Camacho Catalina; Lele Shashi; Odunsi Kunle; Cohen Samantha; Dottino Peter; Martignetti John A (BMC, 2011)
Abstract Background Glutathione peroxidase 3 (GPX3) is a selenocysteine-containing antioxidant enzyme that reacts with hydrogen peroxide and soluble fatty acid hydroperoxides, thereby helping to maintain redox balance within cells. Serum levels of GPX3 have been found to be reduced in various cancers including prostrate, thyroid, colorectal, breast and gastric cancers. Intriguingly, GPX3 has been reported to be upregulated in clear cell ovarian cancer tissues and thus may have implications in chemotherapeutic resistance. Since clear cell and serous subtypes of ovarian cancer represent two distinct disease entities, the aim of this study was to determine GPX3 levels in serous ovarian cancer patients and establish its potential as a biomarker for detection and/or surveillance of papillary serous ovarian cancer, the most frequent form of ovarian tumors in women. Patients and Methods Serum was obtained from 66 patients (median age: 62 years, range: 22-89) prior to surgery and 65 controls with a comparable age-range (median age: 53 years, range: 25-83). ELISA was used to determine the levels of serum GPX3. The Mann Whitney U test was performed to determine statistical significance between the levels of serum GPX3 in patients and controls. Results Serum levels of GPX3 were found to be significantly lower in patients than controls (p = 1 × 10-2). Furthermore, this was found to be dependent on the stage of disease. While levels in early stage (I/II) patients showed no significant difference when compared to controls, there was a significant reduction in late stage (III/IV, p = 9 × 10-4) and recurrent (p = 1 × 10-2) patients. There was a statistically significant reduction in levels of GPX3 between early and late stage (p = 5 × 10-4) as well as early and recurrent (p = 1 × 10-2) patients. Comparison of women and controls stratified to include only women at or above 50 years of age shows that the same trends were maintained and the differences became more statistically significant. Conclusions Serum GPX3 levels are decreased in women with papillary serous ovarian cancer in a stage-dependent manner and also decreased in women with disease recurrence. Whether this decrease represents a general feature in response to the disease or a link to the progression of the cancer is unknown. Understanding this relationship may have clinical and therapeutic consequences for women with papillary serous adenocarcinoma.